Czech Republic : Improving Employment Chances of the Roma - World Bank (Washington, DC, 2014)
Roma in marginalized localities in the Czech Republic have not benefited from the recent improving employment opportunities in the Czech labor market. Employment among Roma is low and labor market participation limited, often driven by lacking labor market opportunities. The labor market status among the Roma is strongly driven by educational attainment and skills, and the vast majority of Roma in marginalized communities suffer from low attainment and lacking functional literacy and numeracy skills. As a result a majority rely on traditionally generous social welfare benefits to make ends meet. In an effort to reduce this welfare trap the Czech Government has introduced measures to reduce benefits and tighten conditions for long-term unemployed who are inactive. However, with very low demand for low or unskilled labor and widespread indebtedness of Roma which acts as a binding barrier to choosing formal employment, this tightening of beneficiaries' incentives alone will not suffice in enhancing their employment chances. It requires effective interventions by the employment services; yet in its current set-up the Czech labor office appears not well placed to provide effective support to long-term unemployed and disadvantaged job-seekers such as Roma. A new approach to improving job chances for socially excluded youth and adults is necessary, involving a new way of engagement through the labor office and contracted third sector service providers and with integrated activation services addressing multiple barriers to employment such as skills deficits, lack of child care, indebtedness and others. However, given the large skills gap of Roma and the receding demand for elementary skills in the labor market, the key long-term strategy to prevent Roma joblessness has to focus on improving educational outcomes for Roma.